Pengaruh Harga dan E-Service Quality terhadap E-Satisfaction di Toko Ninetech pada Marketplace Shopee - Galang Hildan; Arief Budiyanto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the effect of price and e-service quality on e-satisfaction at Ninetech Store on the Shopee marketplace, both partially and simultaneously. This study uses a quantitative method with an associative approach. The research subjects were Ninetech Store customers, with a sample size of 96 respondents obtained through sampling techniques using the Rao Purba formula. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results show that price has a positive and significant effect on e-satisfaction, as does e-service quality, which also has a positive and significant effect on e satisfaction. In addition, price and e-service quality were simultaneously proven to have a significant effect on the e-satisfaction of Ninetech Store customers on the Shopee marketplace. The results of this study are expected to be taken into consideration by Ninetech Store in formulating pricing strategies and improving the quality of electronic services to increase customer satisfaction.